Emerging Ablative and Transarterial Therapies for Pancreatic Cancer - Narayanan, Govindarajan; Ucar, Antonio; Gandhi, Ripal T.; Nasiri, Arian; Inampudi, Prasuna; Wilson, Nicole M.; Asbun, Horacio Jose (Digestive Disease Interventions, 2020)
Pancreatic adenocarcinoma is a highly aggressive malignancy with a poor prognosis secondary to late presentation with metastases, challenging resection, and limited alternative therapies. Standard treatment strategies for pancreatic cancer include surgery, chemotherapy, and radiation therapy. These options can extend survival and/or relieve symptoms but are seldom curative. Thermal ablative therapies have been utilized in pancreatic cancer mostly in an open surgical setting. Irreversible electroporation (IRE) is a nonthermal ablative option for pancreatic cancer that uses high voltage, low energy direct current to induce cell death. IRE technology has been shown to spare critical structures such as blood vessels and bile ducts. The safety and efficacy of the percutaneous IRE in Stage 3 pancreas cancer has been studied and there is currently a Food and Drug Administration approved, randomized, controlled trial, and registry enrolling patients in the United States. Recent animal studies have also demonstrated that the advantages of IRE may extend beyond the local tumor effect. In addition to this local ablative option, a phase 3 trial is studying a transarterial option in the management of pancreatic cancer.
Keywords: pancreas; IRE; nanoknife